Collaborative information behaviour of butterfly farmers in Eastern Usambara Mountains, Tanzania - Ndumbaro, Faraja; M. Mutula, Stephen (Malaysian Journal of Library and Information Science, 2017)
This study investigated collaborative information behaviour of butterfly farmers working in the Integrated Conservation and Development Project (ICDP) located in the neighbourhood of Amani Nature Reserve, Tanzania. The study was motivated by the fact that despite extensive studies on collaborative information behavior in such domains as education, medical, and the military there is a knowledge gap in our understanding of farmers’ collaborative information behavior in the context of collaborative farming. The investigation sought to investigate the shared information needs of farmers in the ICDP project; the patterns of collaborative seeking, sharing and exchanging information of farmers in ICDP; and how butterfly farmers, ANR and TFCG officials in ICDP perceive the link between collaborative farming and collaborative information behaviour. The study applied qualitative approach in analysing group information behaviour guide by the social capital theoretical lens. The data were collected through interviews and observation and analysed using thematic categorisation. The findings of the study revealed that collaborative farming practices, formal structure of relationship between farmers and characteristics farmers were the factors which shaped the way farmers sought, shared and exchanged knowledge and information. It was further revealed that the interplay between collaborative information behaviour and collaborative farming practices were strong enough to support effective implementation of ICDP goals. The study has demonstrated the importance of using social capital factors particularly group structure, embedded resources and shared goals to understand human information behaviour. The findings also shed light to policy and decision makers in the sectors of agriculture and natural resources on the importance of understanding the relationships between information, conservation and development. With regard to practice, the findings have implications to stakeholders engaging on different ICDPs in understanding the role of information on promoting integrated and sustainable agricultural practices.